2014
DOI: 10.1007/s10900-014-9953-4
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Community-Based Health Literacy Intervention for Spanish Speakers

Abstract: The National Action Plan to Improve Health Literacy emphasizes the importance of community-based opportunities for education, such as English as a second language (ESL) programs. It recommends collaborations among the adult literacy and ESL communities. However, limited attention has been given to researching the effectiveness of community-based interventions that combine ESL and health literacy. The purpose of this study was to explore the feasibility of using different community settings for improving health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…Although our survey was written at the sixth grade level, if participants had low literacy, particularly health literacy, they may not have understood the questions as they relate to their health care. 44,45 Women could choose the language of the survey, but we did not collect information on which women were bilingual. As a tertiary referral center, our population may have greater medical complications and need counseling on these issues, not leaving perceived time for GWG counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Although our survey was written at the sixth grade level, if participants had low literacy, particularly health literacy, they may not have understood the questions as they relate to their health care. 44,45 Women could choose the language of the survey, but we did not collect information on which women were bilingual. As a tertiary referral center, our population may have greater medical complications and need counseling on these issues, not leaving perceived time for GWG counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Access to health care is a major barrier in Hispanic communities. A CTSC-funded pilot project addressed barriers to accessing health care 12 using health literacy as a vehicle for teaching English as a second language to Spanish speakers. A HERO who is skilled in teaching health literacy within Hispanic populations was successful in helping the researcher identify and coordinate project sites, conduct focus groups, and recruit participants for the study.…”
Section: Challenge: Overcoming Cultural Barriersmentioning
confidence: 99%
“…8,12,13 New Mexico received a State Innovations Model Design Award from the Centers for Medicare and Medicaid Services. The resulting plan designated HEROs as key regional resources in facilitating links between priority community health needs and health system and social service resources.…”
Section: Outcomes Of the Heros And Ctsc Partnershipmentioning
confidence: 99%
“…Four curricula reported results from evaluations designed to assess their effectiveness in improving students' health literacy Elder et al, 1998Elder et al, , 2000Soto Mas et al, 2014;Soto Mas, Ji, Fuentes, & Tinajero, 2015;Taylor et al, 2009Taylor et al, , 2011. All reported evaluations were conducted by the curriculum developers=personnel.…”
Section: What Are the Goals And Health Topics Of These Curricula?mentioning
confidence: 99%
“…Two evaluation studies reported its effectiveness. The first one (Soto Mas et al, 2014) consisted of a pretest-posttest design assessing students' health literacy with the Spanish version of the Test of Functional Health Literacy in Adults (Parker, Baker, Williams, & Nurss, 1995). The second one (Soto Mas et al, 2015) comprised a randomized control trial, and the results showed a significantly higher increase in scores on the Test of Functional Health Literacy in Adults for the intervention group compared to the control group.…”
Section: What Are the Goals And Health Topics Of These Curricula?mentioning
confidence: 99%